Lady Maggie's secret scandal - Burrowes, Grace (Burrowes, Grace. Windhams., 2020)
When some of her personal letters go missing, Maggie Windham, the illegitimate daughter of the Duke of Moreland, turns to private investigator Benjamin Hazlit to help her recover the letters and stave off potential blackmail.